Chapter PART I. Students' Conversations with Dante (Studi e saggi, 2021)
The creative pieces in this volume reveal the complex relationship that young South African writers have with Dante and his Commedia. Notable for their personal response to the poet, they engage in a process of rewriting Dante, who appears variously as a mirror and as a remote presence against which to measure themselves. Their stories are drawn to the rich implications of Dante's allegory, as it inscribes itself into their personal and political landscapes, offering them an alternative narrative-a new Purgatorial language of change, despair, and hope-in which to frame the South African experience.